PERMINTAAN TAMBAHAN TARIF JASA KURIR DALAM BISNIS DELIVERY ORDER DI KOTA LANGSA (TINJAUAN ETIKA EKONOMI ISLAM) - Firdaus, Muhammad (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2019)
Delivery order is an inter-messaging service, in its mechanism, the customer called the admin delivery to order an item desired and the admin to forward the order via what?s app to the courier. But in practice, the courier sometimes asks for additional fee courier services to consumers for a variety of reasons. The issue in this study, how is the practice additional requests for courier services in order delivery business in Langsa city and how the Islamic economic ethics reviews against additional requests for courier services in delivery order business in Langsa city. This type of research is field research. The results of this research shows, the practice additional fee courier services to consumers is the consumers feel lied. The additional fee practice of courier services is reviewed according to Islamic law is not yet qualified, because in practice the addition of fee made to make consumers or customers are less willing to feel disadvantaged because there is no prior notice (gharar), so the consumer or costomer is forced to pay. In Islam, it has been explained that one of the two people is forced to do the contract, so the contract is not valid.